(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: This study investigated the effect of crude oil (six different concentrations) on seed germination of two plants (Zea mays and Gossipium hirsutum) and the growth of these plants when planted in oil-polluted soil. Total hydrocarbons were measured also. Materials: Six concentrations of crude oil were prepared (2.5, 5, 7.5, 10, 12.5, and 15)%, 10 seeds of both plants were put in petri dishes of each concentration with three replicates. 75 gm of petroleum were mixed with 1 kg of soil; 5 kg of polluted soil were put in pots underlined with aluminum foil; the pots were watered and left for 72 hrs. Then seeds are put in, and plants are harvested after two months. One gram of ground parts of the plant is taken, adding 10 ml of 1:1 solvent (ethanol/ chlorophorm) with shaking for 30 min. Optical density read on (520 nm) . Results: Results showed Z. mays seeds were less tolerant than those of G. hirsutum , the highest significant germination value was of 2.5 % for each plant while the lowest was for the concentration achieved when treated with 15 % for G. hirsutum and 12.5 % for Zea mays . that stem radius, leaf area, and height were significantly reduced as compared with the control. The results showed an accumulation of TH in the plants.